Civic engagement in serious illness, death, and loss: A systematic mixed-methods review. (April 2022) - D'Eer, Louise; Quintiens, Bert; Van den Block, Lieve; Dury, Sarah; Deliens, Luc; Chambaere, Kenneth; Smets, Tinne; Cohen, Joachim
Background: New public health approaches to palliative care such as compassionate communities aim to increase capacity in serious illness, death, and loss by involving civic society. Civic engagement has been described in many domains of health; a description of the characteristics, processes, and impact of the initiatives in palliative care is lacking. Aim: To systematically describe and compare civic engagement initiatives in palliative care in terms of context, development, impact, and evaluation methods. Design: Systematic, mixed-methods review using a convergent integrated synthesis approach. Registered in Prospero: CRD42020180688. Data sources: Six databases (PubMed, Scopus, Sociological Abstracts, WOS, Embase, PsycINFO) were searched up to November 2021 for publications in English describing civic engagement in serious illness, death, and loss. Additional grey literature was obtained by contacting the first authors. We performed a quality appraisal of the included studies. Results: We included 23 peer-reviewed and 11 grey literature publications, reporting on nineteen unique civic engagement initiatives, mostly in countries with English as one of the official languages. Initiatives involved the community in their development, often through a community-academic partnership. Activities aimed to connect people with palliative care needs to individuals or resources in the community. There was a variety of evaluation aims, methods, outcomes, and strength of evidence. Information on whether or how to sustain the initiatives was generally lacking. Conclusions: This is the first review to systematically describe and compare reported civic engagement initiatives in the domain of palliative care. Future studies would benefit from improved evaluation of impact and sustainability.